Implementasi Sistem Informasi Akuntansi Pada Umkm Pabrik Tempe Bapak Welas Depok - Romadhona, Puspita; Yulianti, Wiwit Rohaeni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine the implementation of accounting information systems in Micro, Small, and Medium Enterprises (MSMEs) with respondents from Mr. Welas Tempe Factory in Depok. The type of research used is a case study. Data collection methods in this study are interviews, observations, and documentation. The data analysis method uses a descriptive analysis method with a qualitative approach. The results of data analysis and discussion of this study indicate that Mr. Welas Tempe Factory still uses recording and is only limited to incoming and outgoing money so that Mr. Welas Tempe Factory cannot carry out the application and readiness of the implementation of the accounting information system due to lack of knowledge about accounting and limited human resources who manage bookkeeping.